2017
DOI: 10.1038/s41598-017-04040-w
|View full text |Cite
|
Sign up to set email alerts
|

Improved risk stratification in prevention by use of a panel of selected circulating microRNAs

Abstract: Risk stratification is crucial in prevention. Circulating microRNAs have been proposed as biomarkers in cardiovascular disease. Here a miR panel consisting of miRs related to different cardiovascular pathophysiologies, was evaluated to predict outcome in the context of prevention. MiR-34a, miR-223, miR-378, miR-499 and miR-133 were determined from peripheral blood by qPCR and combined to a risk panel. As derivation cohort, 178 individuals of the DETECT study, and as validation cohort, 129 individuals of the SH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 44 publications
(55 reference statements)
0
19
0
3
Order By: Relevance
“…To date, three studies analyzed the association of miR-223 with clinical endpoints ( 37 39 ). Schulte evaluated 873 individuals and revealed that elevated miR-223 levels reliably predicted future cardiovascular deaths [HR 2.23 per one SD increase (1.20; 4.14), P = 0.011, C-index 0.80], as 2.1% ( n = 18) of the subject experienced cardiovascular death over a median follow-up time of 4 years ( 37 ).…”
Section: Mir-223mentioning
confidence: 99%
See 1 more Smart Citation
“…To date, three studies analyzed the association of miR-223 with clinical endpoints ( 37 39 ). Schulte evaluated 873 individuals and revealed that elevated miR-223 levels reliably predicted future cardiovascular deaths [HR 2.23 per one SD increase (1.20; 4.14), P = 0.011, C-index 0.80], as 2.1% ( n = 18) of the subject experienced cardiovascular death over a median follow-up time of 4 years ( 37 ).…”
Section: Mir-223mentioning
confidence: 99%
“…More recently, Keller et al analyzed a panel of miRNAs to predict outcome in the context of cardiovascular disease prevention. They determined that all-cause 5-year mortality was associated with lower miR-223 levels (HR: 0.30; 95% CI: 0.08–1.07; P = 0.063) ( 39 ). The presented results show that miR-223 may not only serve as a biomarker of platelet activation, but could also be exploited as a prognostic marker.…”
Section: Mir-223mentioning
confidence: 99%
“…A growing evidence elucidates the role of microRNAs (miRs) in development and progression of HCC. Since miRs are released to the circulating blood, their potential value as diagnostic and prognostic markers in HCC have gained more attention [9][10][11][12][13][14]. There is an increasing interest in understanding the association of miR expression in HCC cells with their chemo-and radiosensitivity to increase the efficacy of the treatment modality in HCC patients.…”
Section: Introductionmentioning
confidence: 99%
“…Одним из многообещающих способов улучшения стандартных шкал риска FRS (Framingham Risk Score) -Фрамингемская шкала риска, и SCORE (Systematic COronary Risk Evaluation) -Систематическая оценка коронарного риска, в дополнение к описанным ранее [44], является панель циркулирующих микроРНК -биомаркеров ССЗ, характеризующих различные патофизиологические механизмы, которые играют важную роль в развитии и прогрессировании патологии [45][46][47][48]. Эта работа продемонстрировала, что анализ отдельных микроРНК не обладает прогностической ценностью в отношении смертности от ССЗ, тогда как вся панель способна значительно улучшить существующую стратификацию риска [45].…”
Section: стратегии профилактики будущегоunclassified